Analytical Hierarchy Process for Knowledge Integration - Tajuddin, Nur Ilyana Ismarau; Jabar, Marzanah A.; Abdullah, Rusli; Jusoh, Yusmadi Yah (2018)
This paper presents the design of analytical hierarchy process for Knowledge Integration (KI) in Small Medium Enterprises (SMEs). An Analytical Hierarchy Process (AHP) was used to assist in building the model and help draw decisions. In order to illustrate the application of AHP, there are 3 main factors and 13 sub-factors that determine the decision of tools. In this study, Expert Choice™ software is used to conduct the experimental assessments. The judgments were found to be consistent, precise and justifiable with narrow marginal consistency values.